THE HUBUNGAN BERAT TAS DENGAN NYERI PUNGGUNG BAWAH PADA ANAK SEKOLAH UMUR 12-14 TAHUN DI DENPASAR - Luh Ita Mahendrayani; Susy Purnawati; Nopi Andayani (Bachelor of Physiotherapy and Physiotherapy Profession Study Program, Faculty of Medicine, Udayana University in collaboration with Indonesian Physiotherapy Association (IPA), 2015)
Use of school bags with too much load will cause a variety of musculoskeletal problems such as low back pain. This study aims to determine the relation of bag weight with low back pain in student. Method: This is a cross-sectional study were conducted in May-June 2014. Selected sample in SDN 5 Panjer and SMPN 1 Denpasar using simple random sampling technique which were 123 students of class 6,7, and 8 randomized using a lottery number and obtained 62 samples. Results: Research subjects were aged 12 and 13 years old as much as 37.1%. Thirty-nine girls and 23 boys with an average body mass index category most were underweight as much as 43.5%. Students were carry school bags most severe category of bags are on ?15% of body weight as much as 46.8%. Low back pain experienced by most students who was bring a bag with the category of 6-13kg as much as 38.7%. Based on chi square test was get values of p = 0.001(p<0.05). Conclusion: That means there is a significant association between bag weight with back pain among elementary and junior high school student in SD Negeri 5 Panjer and SMP Negeri 1 Denpasar.